Morphological evaluation of cystitis glandularis - Rau Aarathi; Kini Hema; Pai Radha (Wolters Kluwer Medknow Publications, 2009)
Cystitis cystica and cystitis glandularis (CG) are relatively common appearances in the urinary bladder though CG may occasionally mimic a neoplasm. Microscopically, two types of CG are recognized, the usual type and intestinal type. This study was undertaken to study the morphology of CG and to highlight the differences in morphology between CG and adenocarcinoma. Eleven cases of CG were seen, of which 3 cases showed predominantly CG, usual type and eight cases showed CG of intestinal type. One case of primary adenocarcinoma was included in this study, where the adjacent bladder mucosa showed CG. Evaluation of the histological features of CG, especially intestinal type helps in correct categorization of this lesion and differentiation from adenocarcinoma of the bladder.